O Aeroporto de Congonhas e a cidade de São Paulo: uma história de afinidade e conflitos - Garcia Filho, Osvalter (2015)
This research work was aimed at understanding the process of development and evolution of Congonhas Airport through time, and, thus, discern that the process of its development is intrinsically linked to the development process of the city of Sao Paulo, both in terms of urban space landscape and socioeconomic factors. When one understands that the development and evolution of the airport has influenced its surroundings particularly the district of Moema, a space area in this research work towards which the landing and takeoff runways of the airport are directly aligned one realizes that an urban facility of such a size should have always been the object of specific urban studies and analyses by the urban planners of the city of São Paulo. However, this kind of attention has been lacking throughout the history of the airport, and that has led to several airplane accidents, with the ones which occurred in 1996 and 2007- involving TAM airplanes and resulting in a high number of deaths - being considered the worst plane crashes in Brazil, with great emotional and psychological impact across the state, and the nation as a whole. Thus, this research work, which was conducted based on a geographical perspective, is intended to serve as a basis for other airports whether in development or not in other urban centers